The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.3390/s21082873
|View full text |Cite
|
Sign up to set email alerts
|

HRV Features as Viable Physiological Markers for Stress Detection Using Wearable Devices

Abstract: Stress has been identified as one of the major causes of automobile crashes which then lead to high rates of fatalities and injuries each year. Stress can be measured via physiological measurements and in this study the focus will be based on the features that can be extracted by common wearable devices. Hence, the study will be mainly focusing on heart rate variability (HRV). This study is aimed at investigating the role of HRV-derived features as stress markers. This is achieved by developing a good predicti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 18 publications
0
40
1
Order By: Relevance
“…There are several machine learning approaches that have explored physiologically derived markers in general for stress recognition (MacLaughlin et al, 2011;Dhama et al, 2019;Šalkevicius et al, 2019). From feature-based machine learning paradigms which classify various features extracted from wearable sensors, i. e., sleep quality, and percentage of screen time (Sano and Picard, 2013), or heart rate variability (HRV) (Dalmeida and Masala, 2021), and thermal-video recognition of the Initial Systolic Time Interval (Kumar S. et al, 2021), applying the state-of-the-art StressNet. StressNet consists of a Long Short-Term Memory (LSTM)-based architecture to harness spatial-temporal aspects of a continuous signal.…”
Section: Related Workmentioning
confidence: 99%
“…There are several machine learning approaches that have explored physiologically derived markers in general for stress recognition (MacLaughlin et al, 2011;Dhama et al, 2019;Šalkevicius et al, 2019). From feature-based machine learning paradigms which classify various features extracted from wearable sensors, i. e., sleep quality, and percentage of screen time (Sano and Picard, 2013), or heart rate variability (HRV) (Dalmeida and Masala, 2021), and thermal-video recognition of the Initial Systolic Time Interval (Kumar S. et al, 2021), applying the state-of-the-art StressNet. StressNet consists of a Long Short-Term Memory (LSTM)-based architecture to harness spatial-temporal aspects of a continuous signal.…”
Section: Related Workmentioning
confidence: 99%
“…Feature selection showed that time domain HRV metrics such as RMSSD and AVNN were important features in stress classification. 39 In our study, tree-based extra-tree classifier had highest sensitivity of 84% and an AUC Score of 84% and an accuracy of 77 %. Feature ranking in our study showed that both demographic features such as mental well-being, higher marriage age, joint family type and HRV features including pNNi20, SDNN and RMSSD were the top classifiers that distinguished between subjects reporting burnout/stress and heathy ones.…”
Section: Discussionmentioning
confidence: 47%
“… 21 These ECG-derived HRV features as markers for stress detection have been previously used in ML algorithms such as K-Nearest Neighbour (KNN), Support Vector Machines (SVM), Multilayer Perceptron (MLP), Random Forest (RF) and Gradient Boosting (GB). 39 In a study aimed to detect stress based on HRV features derived from Apple watch, MLP was the best ML model with 75% AUC, 80% Recall and 72% F1 score. Feature selection showed that time domain HRV metrics such as RMSSD and AVNN were important features in stress classification.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of [5] presented a study on the physiological parameters (with particular focus on the heart rate variability (HRV)) that can be extracted from wearable devices to detect stress levels in car drivers. The authors developed a predictive model based on different machine learning (ML) methodologies such as K-Nearest Neighbor (KNN), Random Forest (RF), among others that is able to classify the stress level extracted from ECG-derived HRV features [5]. The techniques proposed by the authors show that the HRV features can act as markers for stress level detection, achieving a recall of 80% with the ML models proposed [5].…”
Section: Contributed Papersmentioning
confidence: 99%
“…The authors developed a predictive model based on different machine learning (ML) methodologies such as K-Nearest Neighbor (KNN), Random Forest (RF), among others that is able to classify the stress level extracted from ECG-derived HRV features [5]. The techniques proposed by the authors show that the HRV features can act as markers for stress level detection, achieving a recall of 80% with the ML models proposed [5].…”
Section: Contributed Papersmentioning
confidence: 99%